Data on analysis of coronary atherosclerosis on computed tomography and (18)F-sodium fluoride positron emission tomography - Kitagawa, Toshiro (Data Brief, 2017)
This article contains the data showing illustrative examples of plaque classification on coronary computed tomography angiography (CCTA) and measurement of (18)F-sodium fluoride ((18)F-NaF) uptake in coronary atherosclerotic lesions on positron emission tomography (PET). We divided the lesions into one of three plaque types on CCTA (calcified plaque, non-calcified plaque, partially calcified plaque). Focal (18)F-NaF uptake of each lesion was quantified using maximum tissue-to-background ratio. This article also provides a representative case with a non-calcified coronary plaque detected on CCTA and identified on (18)F-NaF PET/non-contrast computed tomography based on a location of a vessel branch as a landmark. These complement the data reported by Kitagawa et al. (2017) [1].